(untitled) (Bangladesh Journal of Medical Science, 2020)
Periodontitis is defined as a chronic gum disease with characteristic inflammation attributed byTh1/Th17 showing excessive immune responses and Tregs dysregulation occurring in the macrophages. Several genes and associated pathways have been identified which influence this condition. By deploying bioinformatics approaches and tools, the authors of this paper validated the presence of the responsible genes and identified its pathways. The current study focuses on using these genes as molecular markers and inhibiting their pathways in addition to conditioning the conversion of Th17 cells into Treg cells by introducing stem cell therapy. This study specifically used Wharton jelly or Umbilical cord stem cells therapy in the control and treatment of Periodontitis. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.594-597